Research of the Development of Precision Technology with Macro/Micro Dual-drive - Yang Manzhi; Zhang Chuanwei; Huang Yumei; Zhang Guangpeng; Feng Bin (Jixie chuandong)
In order to comprehensive analysis of research status and existing problems in macro/micro dual-drive technology,the analysis of research status for four commonly drive ways of macro system and two commonly drivers of micro system which used in the technology with macro/micro dual-drive are completed. The existing problems in this research are analyzed based on summary of the research status,such as the research on rotary motion is lags behind linear motion,the volume of macro/micro dual-drive system is large and structure is complex,the control of the system is lags behind the structure design,and achievement transformation is serious lags behind the technology research. As to solve the problems existing in the process of the technology development,the corresponding solutions are presented.